Education, Research, and Economic Growth - Volker Caspari; Jens Rubart; Günther Rehme (Technische Universität Darmstadt, Department of Law and Economics, 2004)
It is obvious that the German economy exhibits a significant decline in economic growth during the last two decades. Although the German economy has still to overcome the burden of the reunification in 1990 it is shown that this burden might be only one reason of this decline. In this study we follow the new growth theory and develop and com-pare indicators for the educational and R&D systems of the U.S. and Germany. In this line, we show that on average the German system can compete with the U.S. one, but a lack of human capital at very high skill levels becomes obvious. This lack, particularly leads to a lower performance of German R&D and could, therefore, possibly explain the decline of the German growth trend.
Keywords: O11; O30; 330; Human Capital; Research and Development; Efficiency of Educational Systems; Sources of Economic Growth; Wirtschaftswachstum; Humankapital; Forschung; Bildungsökonomik; Neue Wachstumstheorie; Vergleich; Schätzung; Deutschland; Vereinigte Staaten